Implications for Cultural Diversity Management (International Journal of Innovative Research in Engineering & Management, 2021)
Maintenance and approval there has been a lot of  acknowledgment for the beneficial elements of corporate  culture convergence in the past two decades. The challenges  and setbacks associated with the management of several  cultural working groups were not properly handled. Practice  managers must grasp when and when monoculture and multi cultural arrangements are suitable. This article analyses  significant empirical findings that may be utilised in  developing effective paradigms in the area of cultural  diversity. The complexity of a more and more dynamic  workplace needs a search for new behaviour control  techniques. In order to understand the complexity of future  multicultural businesses, traditional paradigms that focus  undue emphasis on efficiency and profitability may not be  sufficient. If the emergent drive toward non-hierarchical,  equitable and flat organisational structures is focused further,  it would be a positive step forward. Above all, it is vital to  include and appreciate the potential and problems offered by  different employees.
Keywords: Cultural diversity; Diverse; Group; Management; Members; Minority; Majority; Organizations